2020
DOI: 10.3390/ijerph17041365
|View full text |Cite
|
Sign up to set email alerts
|

Pistol and Rifle Performance: Gender and Relative Age Effect Analysis

Abstract: Background: The sport overrepresentation of early-born athletes within a selection year is called relative age effect (RAE). Moreover, gender performance differences depend on the sport. The main objectives of the study were to compare performances between gender and RAE in precision shooting events. Method: The results of 704 shooters who participated in the most recent World Shooting Championship were compared. Performance was analysed by event (rifle and pistol), gender and category (junior and senior), tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
2
11
0
1
Order By: Relevance
“…by the stronger recoil of the small-bore rifle and the different shooting positions, resulting in a higher technical demand. Results also showed that there was little variation in shot scores between men and women, but this difference was not significant, which has been confirmed previously by various studies in air-rifle and small-bore shooting [4][5][6][7][8]. This finding is of scientific relevance as it allows men and women to be considered as one group and to omit gender as a covariate which can lead to increased statistical…”
Section: Introductionsupporting
confidence: 74%
“…by the stronger recoil of the small-bore rifle and the different shooting positions, resulting in a higher technical demand. Results also showed that there was little variation in shot scores between men and women, but this difference was not significant, which has been confirmed previously by various studies in air-rifle and small-bore shooting [4][5][6][7][8]. This finding is of scientific relevance as it allows men and women to be considered as one group and to omit gender as a covariate which can lead to increased statistical…”
Section: Introductionsupporting
confidence: 74%
“…With regard to the magnitude of the RAE through the athlete’s sport transition process, it seems that the impact tends to decrease as the chronological age of the athlete increases. This occurs not only in team sports ( Bjørndal et al, 2018b ), but also in the context of individual sport disciplines ( Mon-López et al, 2020 ). In the scientific literature, there are several explanations for this phenomenon, but the most plausible is associated with the maturational status of the athlete ( Torres-Unda et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The RAE has been studied from a variety of approaches and with different purposes: to examine its presence in collective and individual sports contexts (Papadopoulou et al, 2019 ; Steidl-Müller et al, 2019 ; Mon-López et al, 2020 ), evaluate their influence on a fixed competition (Saavedra-García et al, 2019 ), check the degree of impact of gender and/or of age/competition categories in clubs or federal organizations (Bjørndal et al, 2018b ; Romann et al, 2018 ), or even through intervention proposals the intention of which was to reduce the possible consequences (Mann and van Ginneken, 2017 ; Hill et al, 2019 ). Currently, it seems that the objective of the research is focused on studies whose aim is to analyze the relationship between the RAE and competition performance in order to know in-depth how the latter can be influenced by this phenomenon.…”
Section: Introductionmentioning
confidence: 99%